High-strength color brick and preparation and construction method thereof
By designing high-strength colored bricks, combining water-permeable parts and wear-resistant parts, and filling with permeable substrates, the problem of unstable use of existing colored bricks in the manhole cover installation frame is solved, and the effect of the manhole cover area being consistent with the appearance of the nearby road surface is achieved.
Patent Information
- Application Number
- CN202411847737.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-25
AI Technical Summary
Existing colored bricks are not suitable for use directly in manhole cover installation frames, especially in areas where sufficient ground foundation support is lacking, making it difficult to ensure that the installed colored bricks can be used stably.
A high-strength colored brick is designed, including a water permeable piece and a wear-resistant piece. The water permeable piece is arranged on the top of the wear-resistant piece. The connection part is combined with the installation groove of the wear-resistant piece to fill the water permeable matrix to enhance the stability and water permeability of the structure.
This high-strength colored brick can be used stably in the manhole cover installation frame, ensuring that the manhole cover area can maintain the same appearance as the nearby road surface, improve building coordination, and optimize the colored brick structure to adapt to the characteristics of the manhole cover installation frame.
Smart Images

Figure CN119686185A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-strength pavement bricks, and in particular relates to a high-strength colored brick and a preparation and construction method thereof. Background Art
[0002] Colored bricks are suitable for beautification of various roads, buildings and other scenes, and are widely used in various types of construction operations. They are widely used in major urban main roads, tourist areas and pedestrian beautification areas, but currently colored bricks are mainly used as surface structures with stable ground foundations. In covering suspended openings or slots such as sewer manhole covers, they are mainly completed by modules poured with concrete by the manhole cover installation frame, which leads to obvious differences in the appearance and shape of the corresponding area from the nearby colored brick pavement, and the appearance is not good enough. The existing colored bricks are not suitable for direct use in the manhole cover installation frame. This is mainly due to the lack of sufficient ground foundation support in these areas. Although the installation frame made of high-strength metal can provide the necessary support, it is affected by uneven stress distribution, cold and hot shrinkage changes, etc., and it is difficult to ensure that the installed colored bricks can be well used. Summary of the invention
[0003] The object of the present invention is to provide a colored brick structure suitable for the aforementioned scenario, and to provide a corresponding preparation and construction method.
[0004] To achieve the above purpose, the present invention adopts the following technical solution.
[0005] A high-strength colored brick, comprising a water-permeable part 1 and a wear-resistant part 2;
[0006] The wear-resistant part 2 is a rectangular structure, with a rectangular installation groove 2a provided on the top, and a water-permeable hole 2b provided in the center of the installation groove 2a;
[0007] The water-permeable member 1 is arranged on the top of the wear-resistant member 2, and a rectangular connecting portion 1a which can be inserted into the mounting groove 2a is arranged at the bottom of the water-permeable member 1. A plurality of water diversion grooves 1b are arranged on the top of the water-permeable member 1, and the water diversion grooves 1b extend from the top center of the water-permeable member 1 to the edge of the water-permeable member 1;
[0008] The front, back, left, and right sides of the connecting portion 1a are 2 to 5 mm away from the inner wall of the mounting groove 2a; the bottom of the connecting portion 1a is 5 to 8 mm away from the bottom of the mounting groove 2a.
[0009] As a further improvement or preferred embodiment of the aforementioned high-strength colored bricks, a plurality of wear-resistant parts 2 are arranged in an array, and adjacent wear-resistant parts 2 and the wear-resistant parts 2 and the external boundaries are isolated by elastic parts 3 .
[0010] As a further improvement or preferred embodiment of the aforementioned high-strength colored bricks, a permeable matrix is filled between the base surfaces of the permeable member 1 and the wear-resistant member 2 and between adjacent wear-resistant members 2 .
[0011] In this application, the wear-resistant parts are prepared based on the following method:
[0012] A1. Raw materials and pretreatment, including: siliceous raw materials composed of ceramic waste residue, which is screened with 180 mesh after being cleaned, dried, ball-milled, and then screened; calcium raw materials composed of finished quicklime; aggregates composed of ceramic waste, which is screened with a particle size of 2 to 5 mm after being cleaned, dried, crushed, and then screened; crystallizing agent composed of silicate cement; activator composed of soda ash;
[0013] A2. Preparation: Select the following raw materials in mass units, including 50 units of siliceous raw materials, 10-15 units of calcium raw materials, 30-35 units of aggregates, 2-5 units of crystallizing agents, and 0.5 units of activators;
[0014] Add siliceous raw materials, calcium raw materials, aggregates, crystallizing agents, and activators in sequence, stir at a low speed for 5 to 10 minutes until they are evenly mixed, then add 10 units of mass fraction of tap water and stir at a low speed for 10 minutes;
[0015] After the mixing is completed, seal the mixture with water for 30 to 120 minutes to keep it moisturized. After the water is fully absorbed, add 5 to 8 units of water for a second mixing and stirring for 30 minutes, and then seal it for moisturizing.
[0016] Weigh the mixed material and press it into shape, the molding pressure is 20 MPa, and the pressing and holding time is 45 s;
[0017] Demoulding, the blank is placed in an autoclave for autoclave curing, with the temperature rising at a rate of 3.5°C to 1000-1100°C, and the pressure maintained at 1.0-1.5MPa for 5-10h;
[0018] The permeable parts are prepared in the following way:
[0019] B1. Raw materials and pretreatment: Recycled sludge composed of urban sludge and water sludge needs to be disinfected and decontaminated, and large particles of impurities therein need to be filtered out, and then naturally piled and dried to a water content of 60-75%;
[0020] The main components of the purchased fly ash are silicon dioxide, aluminum oxide, iron oxide and calcium oxide;
[0021] The recycled mineral materials need to be disinfected, decontaminated, crushed, filtered and dried;
[0022] To recycle construction waste materials, they need to be crushed, filtered, and dried;
[0023] The pore-forming material is selected according to the pore size characteristics, baked to constant weight, crushed according to the required pore size, and screened to remove fine particles;
[0024] B2. Preparation
[0025] Select 25-40 units of recycled sludge, 30-45 units of fly ash, 20 units of recycled mineral materials and recycled construction waste, and 10 units of pore-forming materials measured by mass;
[0026] After the recycled mineral material and the recycled construction waste are fully mixed, 15 units of tap water are added for stirring, and after continuous stirring and mixing, fly ash and pore-forming materials are added in sequence at a uniform speed. After all are added, stirring is continued for 5 to 30 minutes until there are no obviously exposed recycled mineral material and recycled construction waste particles to form a blank;
[0027] The blank is sealed and kept moisturized at 22-25°C for 18-24 hours;
[0028] Use a pressing machine to form a green body, the pressing pressure is 5-20Mpa, and the holding time is not less than 45s;
[0029] Place the green body in a drying chamber at 100-110°C and dry for 12-20 hours;
[0030] The dried green body is placed in a muffle furnace for sintering. The maximum sintering temperature is 1100-1150°C, the heating rate is 1°C / min, and the temperature is kept at 450°C for 1 hour. After reaching the maximum temperature, it is kept for 2-4 hours. After the end, heating is stopped and the furnace is cooled naturally.
[0031] A further improvement or preferred implementation method of the above-mentioned preparation method of high-strength colored bricks is to increase the drying speed by adding 10 to 20 units by mass of fly ash and pretreated pore-forming materials to every 100 units of recycled sludge in order to shorten the drying time, while improving the properties of the permeable bricks. If stronger strength and flexural resistance are required, the amount of fly ash added can be increased, and if stronger water permeability is required, the amount of pore-forming material added can be increased. The drying time is 4 to 8 days, and the water content of the recycled sludge must not exceed 70%.
[0032] A further improvement or preferred implementation of the above-mentioned method for preparing high-strength colored bricks is that the sealing and moisture retention time is 1.5h to 2h.
[0033] A further improvement or preferred implementation of the construction method for the high-strength colored bricks described in claim 2 comprises the following steps:
[0034] Step 1: Clean the installation frame and use clean water to rinse the mud and debris inside and outside the frame;
[0035] Step 2: Lay the wear-resistant parts according to the installation position, and install the elastic parts 3 on the wear-resistant parts and between the wear-resistant parts and the installation frame;
[0036] Step 3: Fill and compact. Fill the gaps between the wear-resistant parts and between the wear-resistant parts and the installation frame with a water-permeable matrix, compact and clean the excess water-permeable matrix.
[0037] Step 4: Install the permeable parts. After laying the permeable matrix in the installation groove, install the permeable parts and tamp them to ensure that they are flush in all directions.
[0038] A further improvement or preferred implementation of the above-mentioned construction method of high-strength colored bricks is that the depth of the installation groove is 10 to 20 mm, and the thickness of the water-permeable matrix layer in the installation cavity is 5 to 10 mm.
[0039] A further improvement or preferred implementation of the above-mentioned construction method of high-strength colored bricks is that the permeable matrix refers to a hard mixed material composed of permeable sand, crushed stone slag, etc.
[0040] Its beneficial effects are:
[0041] The high-strength colored bricks of the present application are suitable for laying and installing in areas such as sewer manhole covers in cooperation with manhole cover installation frames, so that the manhole cover area can have the same appearance as the nearby road surface, ensuring the coordination of regional buildings, and at the same time optimizing the current colored brick structure so that it can adapt to the use characteristics of the manhole cover installation frame, ensuring its long-term and stable use. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a schematic diagram of high-strength colored bricks after installation;
[0043] Figure 2 This is a construction diagram of high-strength colored bricks;
[0044] Figure 3 It is a structural diagram of high-strength colored bricks. DETAILED DESCRIPTION
[0045] The present invention is described in detail below in conjunction with specific embodiments.
[0046] The high-strength colored bricks of the present invention are mainly used as surface construction for structures such as sewer manholes, road openings, and grooves in conjunction with structures such as sewer manhole cover installation frames 5, so as to establish the corresponding areas with the same shape and material as the nearby road surface structures, thereby expanding the construction plan for the corresponding areas.
[0047] like Figure 2 , Figure 3As shown, the high-strength colored bricks used in the present application adopt a combined structure, including a permeable part 1 and a wear-resistant part 2; the permeable part is used as a surface absorption and permeable structure, and adopts a shape consistent with the colored bricks of the nearby road pavement. The wear-resistant part serves as an intermediate part between the permeable part and the manhole cover installation frame 5, and adaptive micro-displacement is performed through the filling layer between adjacent wear-resistant parts and between the wear-resistant parts and the installation frame 5, so that it can offset the micro-deformation caused by the overall force of the manhole cover installation frame 5 and offset the deformation caused by changes in temperature, etc., to ensure the stability of the structure.
[0048] The wear-resistant part 2 is a rectangular structure, with a rectangular installation groove 2a provided on the top, and a water-permeable hole 2b provided in the center of the installation groove 2a;
[0049] The water-permeable member 1 is arranged on the top of the wear-resistant member 2, and a rectangular connecting portion 1a which can be inserted into the mounting groove 2a is arranged at the bottom of the water-permeable member 1. A plurality of water diversion grooves 1b are arranged on the top of the water-permeable member 1, and the water diversion grooves 1b extend from the top center of the water-permeable member 1 to the edge of the water-permeable member 1;
[0050] The front, back, left, and right sides of the connecting portion 1a are 2 to 5 mm away from the inner wall of the mounting groove 2a; the bottom of the connecting portion 1a is 5 to 8 mm away from the bottom of the mounting groove 2a.
[0051] In the installation frame 5 , a plurality of wear-resistant parts 2 are arranged in an array, and adjacent wear-resistant parts 2 and the wear-resistant parts 2 and the external boundary are isolated by elastic parts 3 .
[0052] The elastic member is used to form a space for filling water-permeable sand between the wear-resistant parts and between the wear-resistant parts and the mounting frame 5, and to provide buffering when the structural dimensions change. Similar structures or products such as springs or serpentine elastic metal sheets can be used.
[0053] A water-permeable matrix is filled between the base surfaces of the water-permeable part 1 and the wear-resistant part 2 and between adjacent wear-resistant parts 2 .
[0054] The permeable matrix refers to a hard mixed material composed of permeable sand, crushed stone slag and the like.
[0055] On the one hand, the permeable matrix forms permeable channels to ensure that the accumulated water flowing down through the top permeable parts can flow out smoothly. On the other hand, it forms an elastic filling layer to perform adaptive filling during the installation of the frame 5 and the micro-deformation of the structure, avoiding strong interference between wear-resistant parts and wear-resistant parts and permeable parts, thereby ensuring the stability of the structure during use.
[0056] The present application also provides a preparation process of the aforementioned colored bricks, including wear-resistant parts and water-permeable parts.
[0057] Among them, the wear-resistant parts are prepared based on the following method
[0058] A1. Raw materials and pretreatment, including: siliceous raw materials composed of ceramic waste residue, which is screened with 180 mesh after being cleaned, dried, ball-milled, and then screened; calcium raw materials composed of finished quicklime; aggregates composed of ceramic waste, which is screened with a particle size of 2 to 5 mm after being cleaned, dried, crushed, and then screened; crystallizing agent composed of silicate cement; activator composed of soda ash;
[0059] A2. Preparation: Select the following raw materials in mass units, including 50 units of siliceous raw materials, 10-15 units of calcium raw materials, 30-35 units of aggregates, 2-5 units of crystallizing agents, and 0.5 units of activators;
[0060] Add siliceous raw materials, calcium raw materials, aggregates, crystallizing agents, and activators in sequence, stir at a low speed for 5 to 10 minutes until they are evenly mixed, then add 10 units of mass fraction of tap water and stir at a low speed for 10 minutes;
[0061] After the mixing is completed, seal the mixture with water for 30 to 120 minutes to keep it moisturized. After the water is fully absorbed, add 5 to 8 units of water for a second mixing and stirring for 30 minutes, and then seal it for moisturizing.
[0062] Weigh the mixed material and press it into shape, the molding pressure is 20 MPa, and the pressing and holding time is 45 s;
[0063] Demoulding, the blank is placed in an autoclave for autoclave curing, with the temperature rising at a rate of 3.5°C to 1000-1100°C, and the pressure maintained at 1.0-1.5MPa for 5-10h;
[0064] Based on the above process, under the conditions of sintering temperature of 1050℃, holding time of 5h and molding pressure of 1MPa, the flexural strength and water permeability coefficient of the prepared wear-resistant parts sample are 11.5MPa and 1.95×10-2cm / s respectively. It has excellent flexural strength and strong water permeability, and can maintain its structural integrity during repeated micro-deformation and hot and cold expansion and contraction of the installation frame 5, prevent excessive wear, and meet the use requirements.
[0065] The water-permeable member is prepared in the following manner:
[0066] B1. Raw material pretreatment
[0067] The recycled sludge is composed of urban sludge and water sludge, which needs to be disinfected and decontaminated, and large particle impurities in it need to be filtered. The water content of the recycled sludge exceeds 80%. In order to reduce the water content, it is naturally piled and dried to a water content of 60-75%.
[0068] In particular, in order to shorten the drying time, 10 to 20 units of fly ash and pre-treated pore-forming materials are added to every 100 units of recycled sludge to increase the drying speed and improve the properties of the permeable bricks. If stronger strength and flexural resistance are required, the amount of fly ash added can be increased. If stronger water permeability is required, the amount of pore-forming materials added can be increased. The drying time is 4 to 8 days, and the water content of the recycled sludge must not exceed 70%.
[0069] The fly ash is obtained through purchase, and the main components of the purchased fly ash are silicon dioxide, aluminum oxide, iron oxide, and calcium oxide;
[0070] Recycle the mineral materials, disinfect and decontaminate them, crush them, filter them, and dry them;
[0071] Recycling of construction waste: crushing, filtering, drying;
[0072] The pore-forming material is selected according to the pore size characteristics, baked to constant weight, crushed according to the required pore size, and screened to remove fine particles;
[0073] B2. Preparation: Select 25-40 units of recycled sludge, 30-45 units of fly ash, 20 units of recycled mineral material and recycled construction waste, and 10 units of pore-forming material measured by mass;
[0074] After the recycled mineral material and the recycled construction waste are fully mixed, 15 units of tap water are added for stirring, and after continuous stirring and mixing, fly ash and pore-forming materials are added in sequence at a uniform speed. After all are added, stirring is continued for 5 to 30 minutes until there are no obviously exposed recycled mineral material and recycled construction waste particles to form a blank;
[0075] The blank is sealed and kept moisturized at 22-25°C for 18-24 hours;
[0076] Use a pressing machine to form a green body, the pressing pressure is 5-20Mpa, and the holding time is not less than 45s;
[0077] Place the green body in a drying chamber at 100-110°C and dry for 12-20 hours;
[0078] The dried green body is placed in a muffle furnace for sintering. The maximum sintering temperature is 1100-1150°C, the heating rate is 1°C / min, and the temperature is kept at 450°C for 1 hour. After reaching the maximum temperature, it is kept for 2-4 hours. After the heating is completed, the heating is stopped and the green body is naturally cooled with the furnace.
[0079] Under the conditions of sludge dosage of 25 units, sintering temperature of 1150℃, insulation time of 2h and molding pressure of 10MPa, the flexural strength and water permeability coefficient of the prepared permeable specimens were 9.1MPa and 2.8×10-2cm / s respectively, which have high flexural strength and excellent water permeability. The metal dissolution of recycled mineral materials containing heavy metals is far lower than the upper limit specified for pavement bricks. It has high safety and can effectively realize the extraction of moisture from the pavement. At the same time, the hardness and surface adhesion are sufficient to meet the use requirements as ground colored bricks.
[0080] like Figure 1 , Figure 2 As shown, the present application also provides a construction method of the aforementioned colored bricks in combination with the manhole cover installation frame 5, comprising the following steps:
[0081] Step 1: Clean the installation frame 5 and use clean water to rinse the mud and debris inside and outside the frame;
[0082] Step 2: Lay the wear-resistant parts according to the installation position, and install the elastic parts 3 on the wear-resistant parts and between the wear-resistant parts and the installation frame 5;
[0083] Step 3: Fill and tamp, fill the gaps between the wear-resistant parts and between the wear-resistant parts and the mounting frame 5 with a water-permeable matrix, tamp and clean up excess water-permeable matrix;
[0084] Step 4: Install the permeable parts. After laying the permeable matrix in the installation groove, install the permeable parts and tamp them to ensure that they are flush in all directions.
[0085] The depth of the installation groove is 10-20 mm, and the thickness of the water-permeable matrix layer in the installation cavity is 5-10 mm.
[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A high-strength colored brick, characterized in that: It comprises a water-permeable part (1) and a wear-resistant part (2); The wear-resistant part (2) is a rectangular structure, a rectangular installation groove (2a) is arranged on the top, and a water-permeable hole (2b) is arranged at the center of the installation groove (2a); The water permeable member (1) is arranged on the top of the wear-resistant member (2); a rectangular connecting portion (1a) which can be inserted into the installation groove (2a) is arranged at the bottom of the water permeable member (1); a plurality of water diversion grooves (1b) are arranged on the top of the water permeable member (1); the water diversion grooves (1b) extend from the center of the top of the water permeable member (1) to the edge of the water permeable member (1); The front, back, left and right sides of the connecting portion (1a) are respectively 2 to 5 mm away from the inner wall of the mounting groove (2a); and the bottom of the connecting portion (1a) is 5 to 8 mm away from the bottom of the mounting groove (2a).
2. The high-strength colored brick according to claim 1, characterized in that: A plurality of wear-resistant parts (2) are arranged in an array, and adjacent wear-resistant parts (2) and the wear-resistant parts (2) and the external boundary are isolated by elastic parts (3).
3. The high-strength colored brick according to claim 1, characterized in that: A water-permeable matrix is filled between the base surfaces of the water-permeable part (1) and the wear-resistant part (2) and between adjacent wear-resistant parts (2).
4. A method for preparing the high-strength colored brick according to claim 1, characterized in that: Wear-resistant parts are prepared based on the following method A1. Raw materials and pretreatment, including: siliceous raw materials composed of ceramic waste residue, which is screened with 180 mesh after being cleaned, dried, ball-milled, and then screened; calcium raw materials composed of finished quicklime; aggregates composed of ceramic waste, which is screened with a particle size of 2 to 5 mm after being cleaned, dried, crushed, and then screened; crystallizing agent composed of silicate cement; activator composed of soda ash; A2. Preparation: Select the following raw materials in mass units, including 50 units of siliceous raw materials, 10-15 units of calcium raw materials, 30-35 units of aggregates, 2-5 units of crystallizing agents, and 0.5 units of activators; Add siliceous raw materials, calcium raw materials, aggregates, crystallizing agents, and activators in sequence, stir at a low speed for 5 to 10 minutes until they are evenly mixed, then add 10 units of mass fraction of tap water and stir at a low speed for 10 minutes; After the mixing is completed, seal the mixture with water for 30 to 120 minutes to keep it moisturized. After the water is fully absorbed, add 5 to 8 units of water for a second mixing and stirring for 30 minutes, and then seal it for moisturizing. Weigh the mixed material and press it into shape, the molding pressure is 20 MPa, and the pressing and holding time is 45 s; Demoulding, the blank is placed in an autoclave for autoclave curing, with the temperature rising at a rate of 3.5°C to 1000-1100°C, and the pressure maintained at 1.0-1.5MPa for 5-10h; The permeable parts are prepared in the following way: B1. Raw materials and pretreatment: Recycled sludge composed of urban sludge and water sludge needs to be disinfected and decontaminated, and large particles of impurities are filtered out, and then naturally piled and dried to a moisture content of 60-75%; The main components of the purchased fly ash are silicon dioxide, aluminum oxide, iron oxide and calcium oxide; The recycled mineral materials need to be disinfected, decontaminated, crushed, filtered and dried; To recycle construction waste materials, they need to be crushed, filtered, and dried; The pore-forming material is selected according to the pore size characteristics, baked to constant weight, crushed according to the required pore size, and screened to remove fine particles; B2. Preparation Select 25-40 units of recycled sludge, 30-45 units of fly ash, 20 units of recycled mineral materials and recycled construction waste, and 10 units of pore-forming materials measured by mass; After the recycled mineral material and the recycled construction waste are fully mixed, 15 units of tap water are added for stirring, and after continuous stirring and mixing, fly ash and pore-forming materials are added in sequence at a uniform speed. After all are added, stirring is continued for 5 to 30 minutes until there are no obviously exposed recycled mineral material and recycled construction waste particles to form a blank; The blank is sealed and kept moisturized at 22-25°C for 18-24 hours; Use a pressing machine to form a green body, the pressing pressure is 5-20Mpa, and the holding time is not less than 45s; Place the green body in a drying chamber at 100-110°C and dry for 12-20 hours; The dried green body is placed in a muffle furnace for sintering. The maximum sintering temperature is 1100-1150°C, the heating rate is 1°C / min, and the temperature is kept at 450°C for 1 hour. After reaching the maximum temperature, it is kept for 2-4 hours. After the end, heating is stopped and the furnace is cooled naturally.
5. The method for preparing high-strength colored bricks according to claim 4, characterized in that: In order to shorten the drying time, 10 to 20 units of fly ash and pretreated pore-forming materials are added to every 100 units of recycled sludge to increase the drying speed and improve the properties of permeable bricks. If stronger strength and flexural resistance are required, the amount of fly ash added can be increased. If stronger water permeability is required, the amount of pore-forming materials added can be increased. The drying time is 4 to 8 days, and the moisture content of the recycled sludge must not exceed 70%.
6. The method for preparing high-strength colored bricks according to claim 4, characterized in that: The sealing and moisturizing time is 1.5h to 2h.
7. A construction method for the high-strength colored bricks according to claim 2, characterized in that: The steps include: Step 1: Clean the installation frame and use clean water to rinse the mud and debris inside and outside the frame; Step 2: Lay the wear-resistant parts according to the installation position, and install elastic parts (3) on the wear-resistant parts and between the wear-resistant parts and the installation frame; Step 3: Fill and compact. Fill the gaps between the wear-resistant parts and between the wear-resistant parts and the installation frame with a water-permeable matrix, compact and clean the excess water-permeable matrix. Step 4: Install the permeable parts. After laying the permeable matrix in the installation groove, install the permeable parts and tamp them to ensure that they are flush in all directions.
8. The construction method of high-strength colored bricks according to claim 1, characterized in that: The depth of the installation groove is 10-20 mm, and the thickness of the water-permeable matrix layer in the installation cavity is 5-10 mm.
9. The construction method of high-strength colored bricks according to claim 1, characterized in that: The permeable matrix refers to a hard mixed material composed of permeable sand, crushed stone slag and the like.